2006
DOI: 10.1111/j.1745-4549.2006.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and Evaluation of Chocolate Bars From Roasted and Unroasted African Breadfruit, and Bambara Groundnut Flours

Abstract: Bambara groundnut (Voandezia subterranea) and African breadfruit (ABF) (Treculia africana) were procured, and then processed into flours by roasting or without roasting. The flours and cocoa powder were analyzed for functional properties. The flours of 25, 20 or 15 g were mixed with 15, 20 and 25 g of cocoa powder plus 40-g sugar, 30-g milk and 10-g margarine, respectively, and heated for 20 or 10 min, then molded into bars. The chocolate bars produced were evaluated for nutrient composition and sensory proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…With the addition of white maize fiber content improves in cereal bars (Utrilla‐Coello, Acevedo, Osorio‐Diaz, Tovar, & Bello‐Perez, ). Similarly, addition of legume flours increased protein, fat, fiber, ash, minerals, and vitamins in chocolate bars (Onwuka & Abasiekong, ). In another study, apple bars supplemented with soy have been found to be a good snack food used to enhance protein level and availability (Agrahari, Khurdna, Lata, Kaur, & Kapoor, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of white maize fiber content improves in cereal bars (Utrilla‐Coello, Acevedo, Osorio‐Diaz, Tovar, & Bello‐Perez, ). Similarly, addition of legume flours increased protein, fat, fiber, ash, minerals, and vitamins in chocolate bars (Onwuka & Abasiekong, ). In another study, apple bars supplemented with soy have been found to be a good snack food used to enhance protein level and availability (Agrahari, Khurdna, Lata, Kaur, & Kapoor, ).…”
Section: Resultsmentioning
confidence: 99%
“…No significant variation has been observed in crude protein, crude fat, ash, and NFE contents among various bar samples during storage (Table 3). However, crude protein, crude fiber, and ash con- (Onwuka & Abasiekong, 2006). In another study, apple bars supplemented with soy have been found to be a good snack food used to enhance protein level and availability (Agrahari, Khurdna, Lata, Kaur, & Kapoor, 2004).…”
Section: Proximate Analyses Of Date Barsmentioning
confidence: 99%
“…A candy bar fortified with soy protein contained 58.7% carbohydrates, 12.4% protein, and 9% fat [ 29 ]. Similarly, the addition of legume flours increases protein, fat, fiber, ash, minerals, and vitamins in chocolate bars [ 34 ]. In the present scanario, high-energy fortified date bars have been developed with an excellent profile of protein, carbohydrate, and fat.…”
Section: Discussionmentioning
confidence: 99%
“…(7) In Eastern Africa, bambara groundnuts are roasted, milled, and the flour is used to make a soup, a relish, and also a substitute for coffee. (26) HTC bambara groundnuts require longer boiling time (namely 3-4 hours), (7) and therefore higher-energy expenditure to become edible as compared to cowpea or common bean (Phaseolus vulgaris). (5) Cooking time of other legumes is reported to be: for soybean (Glycine max) 3.6 hours, (27) common bean 1.5 hours, (28) cowpea 2.4 hours, (29) and mung bean (Vigna radiata) 0.5 hours.…”
Section: Introductionmentioning
confidence: 99%